Assessment of Groundwater Quality Using Water Quality Indices: A Case Study of Paliganj Distributary, Bihar, India - Praveen, K.; Roy, L. B. (Engineering, Technology & Applied Science Research, 2022)
Groundwater quality evaluation in the command area of Paliganj distributary of the Sone irrigation scheme in India was carried out during two different seasons in the year 2020, namely pre-monsoon, i.e. during March, and post-monsoon, i.e. during October. Forty groundwater samples were obtained from hand pumps and dug wells in the study area during the pre- and post-monsoon seasons. The chemical characteristics of groundwater samples were determined according to American Public Health Association approved process. Twelve parameters, namely, pH, EC, TDS, Ca, Mg, Na, F, SO4, K, Cl, and HCO3 were used to compute the water quality based on the weighted arithmetic water quality index method. In the study area, Ca2+-Mg+-HCO3−, and Ca2+-Mg+-Na+-HCO3- were the dominant hydro-chemical facies. All the samples were found to belong to the excellent to good category for drinking purposes during the pre-monsoon period. However, during the post-monsoon season, only 75% of the samples fell into the excellent to good group, while the remaining 25% fell into the poor for drinking purposes category. By analyzing through the irrigation quality index, 80% of the samples are considered highly suitable for irrigation and the remaining 20% come under the medium category. Thus, it was seen that the majority of groundwater samples are suitable for drinking and irrigation purposes, although groundwater in some portions of the area had high salinity and the Sodium Adsorption Ratio (SAR), showing that it is unsuitable for irrigation and requires adequate drainage.